From colostomy creation to full enteral feeding in neonates with an anorectal malformation: evaluating the role of central venous access - Huijgen, D.; Schokker-van Linschoten, I. K.; Versteegh, H. P.; Sloots, C. E. J. (Frontiers in Surgery, 2025)
PurposeAfter creating a colostomy in newborns with anorectal malformations (ARMs), reaching full enteral feeding may take longer than expected, resulting in an unanticipated period of starvation. This retrospective cohort study aimed to evaluate the postoperative course regarding enteral feeding tolerance and the necessity for a central venous access device (CVAD) after colostomy formation in newborns with ARMs.MethodsThe files of neonates with ARMs who underwent colostomy formation between January 2014 and August 2023 were reviewed. The primary outcome was the postoperative tolerance of enteral feeding. Secondary outcomes were the need for a CVAD and CVAD-related complications.ResultsThirty-four neonates with an ARM underwent colostomy formation. Enteral feeding was initiated on median postoperative day two (IQR 1–2). Full enteral feeding was reached on median postoperative day six (IQR 4–8). In nine neonates (26.5%), it took more than seven postoperative days to reach full enteral feeding, of whom seven (77.8%) had one or more comorbidities that could affect neonatal feeding tolerance. A CVAD was placed in 17 neonates (50%), of whom four (23.5%) needed additional general anesthesia for its placement. There were one or more CVAD-related complications in seven of 17 (41.2%) neonates, mainly involving suspicion of mild catheter-related infections.ConclusionsThe majority of neonates undergoing colostomy formation for an ARM require more than five days to achieve full enteral feeding. It is recommended to bridge this period of inadequate feeding with either fluids or parenteral nutrition by inserting a CVAD during colostomy formation, particularly for those with comorbidities affecting neonatal feeding tolerance.